1984
DOI: 10.1143/jjap.23.628
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature-Dependent Diffusion Mechanism of Zn in InP Using the Semiclosed Diffusion Method

Abstract: A novel semiclosed diffusion technique for III-V semiconductors has been developed giving ease of control of the operating and junction depth. The secondary-ion mass-spectrometry atom profiles and carrier-concentration profiles have been used to develop a mechanism involving the temperature dependence of neutral Zn formation. Doubly-ionized interstitials are thought to be the diffusion species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Theoretical analysis of Zn diffusion shows that the activation energy of Zn in InP is 1.25 eV for the diffusion through the interstitial site and 0.37 eV through the substitutional site. 9 The experimentally obtained activation energy of Zn in InP was 1.63 eV in the case of closedampoule diffusion. 10 In our case, the activation energy is close to that of the diffusion through the substitutional site.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Theoretical analysis of Zn diffusion shows that the activation energy of Zn in InP is 1.25 eV for the diffusion through the interstitial site and 0.37 eV through the substitutional site. 9 The experimentally obtained activation energy of Zn in InP was 1.63 eV in the case of closedampoule diffusion. 10 In our case, the activation energy is close to that of the diffusion through the substitutional site.…”
Section: Resultsmentioning
confidence: 96%
“…This diffusion mechanism needs higher activation energy than diffusion through the substitutional site. 9 On the contrary, the sample annealed at 450°C shows a relatively high, deep-level transition peak. It was reported that the deep level remains as an effective recombination center even at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, creating ohmic contacts to the p-type InP NWs becomes increasingly difficult the lower the doping 9 . An alternative pathway for doping is indiffusion of dopants from gas phase at high temperatures, which has been extensively studied for thin films [9][10][11][12][13][14][15][16] , but has been applied to NWs only recently for materials including InAs 17,18 , Si 19,20 and ZnO 21 . With diffusion doping, electrical transparency to the NW contacts can be increased significantly via high carrier concentrations near the surface 17,19 .…”
Section: This Is the Preprint Author Manuscript Ofmentioning
confidence: 99%
“…21 The often observed high diffusivity of Zn atoms would seem to restrict the possibility of getting abrupt doping profiles. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] However, doping superlattices ͑so-called nipi structure͒ with Zn as p-type dopant have been successfully fabricated. [22][23][24][25] Furthermore, a small Zn diffusion coefficient of 6.5ϫ10 Ϫ14 cm 2 /s has been reported in the case of unin-tentional diffusion.…”
Section: Introductionmentioning
confidence: 99%